Influence of field dependent form of collision integral on kinetic coefficients - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The kinetic equation is turned out in the form that contains collision integral obviously dependent on the value of external electric and magnetic fields. The correspondent calculation of kinetic coefficients shows that for the case considered here they depend evidently on the ratio of average deBroighle wavelength and free-path length. Just here, the real possibility appears to reasonably separate physical kinetics by the classic and non-classic (quantum) ones.